Analysis of Sayang-Sayang Spring Water Quality Using the Water Quality Index for Evaluation of the Suitability of Clean Water Sources - Hismi Susane; Mulhidin Mulhidin; Nurhidayah Nurhidayah; Hijriati Sholehah (Indonesian Journal of Chemistry and Environment, 2025)
Clean water plays a crucial role in public health and environmental sustainability, particularly in urban and peri-urban areas that still rely on springs as a water source. The Sayang-Sayang Spring in Mataram City is utilized by the community, but its water quality is potentially affected by anthropogenic activities in the surrounding area. This study aimed to comprehensively evaluate the water quality of Sayang-Sayang Spring using the Water Quality Index (WQI) approach and determine its suitability as a clean water source. Water samples were collected in August 2025 and analyzed for physical, chemical, and biological parameters in accordance with Minister of Health Regulation No. 32 of 2017. The Weighted Water Quality Index (WQI) was calculated by determining parameter weights using the Delphi method. The analysis results showed that most physical and chemical parameters, such as temperature, TSS, TDS, pH, BOD, DO, nitrate, and ammonia, met clean water quality standards. However, COD and total phosphate values ​​exceeded the established threshold, and microbiological parameters showed a total coliform content of 240 MPN/100 mL. A WQI of 90.20 indicates excellent water quality. However, the presence of organic matter, nutrients, and coliforms limits the use of this spring as untreated drinking water. This study confirms the effectiveness of the WQI as a water quality assessment tool and supports the sustainable management of the spring from anthropogenic pressures.